Antihyperglycemic Activity and Safety Assessment of the Aqueous Extract of Aerial Parts of Scorzonera undulata ssp deliciosa in Rat - Ajebli, Mohammed; Amssayef, Ayoub; Eddouks, Mohamed (Cardiovascular & Haematological Disorders - Drug Targets, 2020)
Aims: The aim of this study was to evaluate the antidiabetic effect of Scorzonera undulata. Background: Scorzonera undulata ssp deliciosa, locally known as “Guiz”, is used as a phytomedicine in Morocco and Algeria to treat different health problems. Interestingly, it is used in the Moroccan pharmacopeia to treat diabetes. To our knowledge, this medicinal herb has never been investigated for any pharmacological activity. Objective: This study aimed to evaluate the antihyperglycemic effect of the aqueous extract of the aerial part of Scorzonera undulata (SUAP) in normal and STZ-induced diabetic rats and to assess the acute toxicity of this extract in Wistar rats. Methods: This study investigated the effects of SUAP at a dose of 20 mg/kg on blood glucose levels in normal and streptozotocin(STZ)-induced diabetic rats. The acute toxicity of SUAP was examined according to the OECD test guideline; rats were divided into four groups of each sex and orally received the SUAP (1000, 2000, or 3000 mg/kg BW). Post-treatment, body weight, signs of toxicity, and/or mortality were observed during 14 days. Other assays such as histopathological examination, preliminary phytochemical investigation, determination of glycogen content and evaluation of α-amylase were performed according to standard protocols. Results: The findings of the current study depicted that both single and repeated oral administration of SUAP (20 mg/kg) generated a significant fall in the blood glucose levels in diabetic rats. A single oral administration of SUAP (at the highest dose of 3000 mg/kg BW) had no significant acute toxicological effects, and oral LD50 of SUAP was greater than 3000 mg/kg. Furthermore, repeated oral administration of SUAP during 15 days led to an increase in the liver glycogen content in diabetic rats to improve the histopathological structure of the liver and pancreas in SUAPtreated diabetic rats and to ameliorate some biochemical parameters such as ALT and creatinine. SUAP had no effect on α-amylase activity. In addition, the preliminary phytochemical investigation showed the richness of the roots of SUAP in some phytochemicals, particularly the polyphenols. Conclusion: The present study demonstrates the antihyperglycemic effect of Scorzonera undulata in diabetic rats which could be involved through the improvement of liver structure and function. In addition, the dose used is not toxic. Finally, the extract contains large amounts of bioactive compounds, mainly polyphenols.
Keywords: glycogen